Objektivitas teologi Islam di era society - Hamdani, Abdillah Hakam (Maliki Interdisciplinary Journal, 2024)
Islamic theology is a area of study that discusses the understanding and interpretation of Islamic religious teachings. Theology involves the study of the essence of human belief, theological concepts, and its implications in the life of a Muslim. Theological concepts in Islam include (faith), tawhid (belief in the oneness of God), nubuwah (prophecy), angels, books revealed by God, qadar (fate), and the afterlife. Faith is the most important foundation in Islamic theology, with belief in Allah as the creator of the universe and the source of all things. The concept of monotheism emphasizes the oneness of Allah and the rejection of allegiance to Allah. Nubuwah refers to a series of prophets starting from Prophet Adam to Prophet Muhammad. In addition, Islamic theology includes belief in angels, holy books such as the holy qur’an and the Bible, as well as belief in destiny and life in the afterlife. However, in theology we often find differences so that several sects have emerged in Islam. This phenomenon has become commonplace because theology depends on the point of view. In preparing this article the author used a qualitative approach where the technique is collecting research data which is carried out by understanding something by utilizing various published materials. Such as magazines, books, notes, documents and internet journals.